REPLACEMENT OF COMMERCIAL RATIONS WITH Hermetia illucens FOR BROILER NUTRIENT DIGESTIBILITY - N. K. S. P., Dewi; Astawa, I P. A.; Mahardika, I G. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims to determine the effect of adding Hermetia illucens in the ration on broiler digestibility. This research was conducted in Nyitdah Village, Kediri District, Tabanan Regency and at the Animal Feed and Nutrition Laboratory, Faculty of Animal Husbandry, Udayana University for 3 months. The research design used was a completely randomized design (CRD) consisting of four treatments and four replications, each replication containing four broilers The treatment given was broilers which were fed without the addition of Hermetia illucens (P0/control); broilers given 5% Hermetia illucens as a substitute for 5% commercial feed (P1); broilers given 10% Hermetia illucens as a substitute for 10% commercial feed (P2) and broilers are given 15% Hermetia illucens as a substitute for 15% commercial feed (P3). The variables observed were dry matter digestibility, organic matter digestibility, crude fiber digestibility and crude protein digestibility. The results showed that broilers treated with P1, P2, and P3 showed results that were not significantly different (P>0.05) from KcBK, KcBO, KcSK and KcPK with P0. Based on the results of this study it can be concluded that replacing commercial rations with Hermetia illucens gives the same results on nutrient digestibility in broilers.